2013
DOI: 10.1016/j.kjms.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of agomelatine in a murine model of obsessive–compulsive disorder: Interaction with meta‐chlorophenylpiperazine, bicuculline, and diazepam

Abstract: The anticompulsive potential of agomelatine, a potent MT1/2 receptor agonist, and its combined effect with m-chlorophenylpiperazine hydrochloride (mCPP), bicuculline, and diazepam, were investigated in male C57BLJ/6 mice using marble-burying behavior (MBB) test. Acute administration of agomelatine (30-40 mg/kg, intraperitoneal (i.p.)) significantly inhibited the MBB in mice without influencing their locomotor activity. Further, chronic (28 days) administration of lower doses of agomelatine (10 and 20 mg/kg, i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Namely, mCPP, a 5-HT2C agonist, which in humans, has been observed to exacerbate symptoms of OCD in untreated patients (Gross-Isseroff et al, 2004) and in rodent RRBs (Reimer et al, 2018). Most studies exploring mCPP have observed increases in stereotypic behavior, commonly evaluated through repetitive grooming and marble burying and particularly at higher doses of 1 and 3 mg/kg (Bhutada et al, 2013;Wright and Rodgers, 2014). Moreover, Kantor et al (2000) observed self-grooming behavior during a social interaction paradigm, finding that administration of mCPP in three separate rat strains enhanced self-grooming.…”
Section: -Ht2cmentioning
confidence: 99%
“…Namely, mCPP, a 5-HT2C agonist, which in humans, has been observed to exacerbate symptoms of OCD in untreated patients (Gross-Isseroff et al, 2004) and in rodent RRBs (Reimer et al, 2018). Most studies exploring mCPP have observed increases in stereotypic behavior, commonly evaluated through repetitive grooming and marble burying and particularly at higher doses of 1 and 3 mg/kg (Bhutada et al, 2013;Wright and Rodgers, 2014). Moreover, Kantor et al (2000) observed self-grooming behavior during a social interaction paradigm, finding that administration of mCPP in three separate rat strains enhanced self-grooming.…”
Section: -Ht2cmentioning
confidence: 99%
“…Another study, in 2013, also highlighted the potential anticompulsive effect of agomelatine [79]. Anticompulsive effect of agomelatine is reported to be mediated via 5HT2C antagonism and MT1/2 agonism [79].…”
Section: Obsessive-compulsive Disordermentioning
confidence: 99%
“…Another study, in 2013, also highlighted the potential anticompulsive effect of agomelatine [79]. Anticompulsive effect of agomelatine is reported to be mediated via 5HT2C antagonism and MT1/2 agonism [79]. Thus, melatonergic agents could be promising and may be developed for possible use in OCD in conjunction with existing medications.…”
Section: Obsessive-compulsive Disordermentioning
confidence: 99%